Selective cleavage of AChR cRNAs harbouring mutations underlying the slow channel myasthenic syndrome by hammerhead ribozymes. - Abdelgany, A; Ealing, J; Wood, M; Beeson, D (2005)
Slow channel congenital myasthenic syndrome (SCCMS) is a dominant disorder caused by missense mutations in muscle acetylcholine receptors (AChR). Expression from mutant alleles causes prolonged AChR ion-channel activations. This 'gain of function' results in excitotoxic damage due to excess entry of calcium ions that manifests as an endplate myopathy. The biology of SCCMS provides a model system to investigate the potential of catalytic nucleic acids for therapy in dominantly inherited disorders involving single missense mutations. Hammerhead ribozymes can catalytically cleave RNA transcripts in a sequence-specific manner. We designed hammerhead ribozymes to target transcripts from four SCCMS mutations, alphaT254I, alphaS226F, alphaS269I and epsilonL221F. Ribozymes were incubated with cRNA transcripts encoding wild type and mutant AChR subunits. The ribozymes efficiently cleaved the mutant allele cRNA transcripts but left the wild type cRNA intact. Cleavage efficiency was optimised for alphaS226F. We were able to demonstrate robust catalytic activity under simulated physiological conditions and at high Ca(2+) concentrations, which is likely to be accumulated at the endplate region of the SCCMS patient muscles. These results demonstrate the potential for gene therapy applications of ribozymes to specifically down-regulate expression of mutant alleles in dominantly inherited disorders.